Effects of Community-Based Psychological Interventions on Depressive Symptoms and Blood Glucose Control for Older Individuals with Type 2 Diabetes: A Systematic Review and Meta- Analysis - Yu, Heajin; Hwang, Boyoung (Seuteureseu yeon-gu (Online), 2020)
Background: To review the effects of community-based psychological interventions on depressive symptoms and blood glucose levels of older individuals with type 2 diabetes (T2D). Methods: A literature search was conducted using seven electronic databases (CINAHL, EMbase, PubMed, CENTRAL, KoreaMed, KISS, and KMbase). The main search terms were ‘diabetes’, ‘depression’, ‘older adult’, and ‘psychological intervention’. The search was restricted to peer-reviewed RCTs published between January 1, 2008 and July 31, 2018. Results: Five studies with a total of 596 participants met the inclusion criteria. Four studies that were included in the meta-analysis incorporated some form of behavioral strategies. Depressive symptoms were measured in four of the five studies, and HbA1c was measured in two of the five studies. The pooled SMD for depressive symptoms was −0.13 (95% CI, −0.31, 0.04; p=0.13) and −0.63 (95% CI, −0.98, −0.28; p＜0.001) for HbA1c. Conclusions: This review highlights the need for additional clinical trials for psychological interventions in older individuals with T2D, especially trials on a larger scale with a wider geographical scope. KCI Citation Count: 2